Evaluation of QT Liability for PF‐05251749 in the Presence of Potential Circadian Rhythm Modification. (25th December 2019) - Huh, Yeamin; Chen, Danny; Riley, Steve; Chang, Cheng; Nicholas, Timothy
Abstract : PF‐05251749 is a dual inhibitor of casein kinase 1 δ/ε, key regulators of circadian rhythm. As a result of its mechanism of action, PF‐05251749 may also change the heart rate corrected QT (QTc) circadian rhythm, which may confound detection of drug‐induced QTc prolongation. In this analysis, a nonlinear mixed effect model including a multioscillator function was developed in addition to fitting the prespecified linear mixed effect concentration‐QTc model, to identify QTc liability of PF‐05251749 in the presence of potential circadian rhythm change. The modeling results suggested lack of clinically meaningful QTc prolongation (upper bound of 90% confidence interval for ∆∆QTc < 10 milliseconds) and that the drug‐induced QTc circadian rhythm change was not present. However, simulation results indicated that inference of drug‐induced QTc prolongation could be misleading if the drug effect on QTc circadian rhythm is not properly addressed. The modeling and simulation results suggest that prespecification of the concentration‐QTc model should be reconsidered for drugs with circadian rhythm modulation potential.